Air Purification in Sustainable Buildings - Staszowska, Amelia (Problemy Ekorozwoju, 2020)
This paper concerns the issue of indoor air purification techniques in sustainable public buildings and the residential sector. One of the requirements of sustainable construction is to reduce the energy costs, minimize waste, improve the well-being of users and create green space. The most important certification systems for green (ecological) buildings such as LEED or BREEAM also include the assessment of the indoor environment in terms of the air quality, noise level, building acoustics and energy consumption. Traditional air treatment and purification systems require the use of numerous devices, air transport systems, which are energy-consuming. It is necessary to clean or replace the working elements periodically. The alternative is biophilic installations (green walls) based on the natural properties of plants for removing gaseous pollutants, particulate matter and even bioaerosols from the air. Plants improve humidity, regulate the carbon dioxide concentration, ionize the air and suppress noise. However, the processes of photocatalytic degradation of gaseous compounds are a very promising method of removing impurities, due to low costs, mild process conditions (temperature and pressure) and the possibility of complete mineralization of impurities.